The tortuous route of the street hawkers in Macao: tales of persistence from the 1950’s to 2015 - Kam, Pui Han (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Post-Colonial Imaginary & Politics of Representation in the Macao SAR: The TEATRAU (Theatre showcase from Portuguese-speaking countries) & the (Re) emergence of 'Lusofonia' under Chinese stars - Morais, Isabel (Theatre 15 China, India & the Eastern World, 2016)

The neglected heritage of the religious resources in Macao SAR: a feasibility study on developing religious tourism - Wong, Ka Lai (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

The Introduction of Smallpox Vaccinations in the Pearl River Delta Region - Morais, Isabel (200th Anniversary of Smallpox Vaccines in the Pearl River Delta. Volume 1, 2007)

The Inquisition in Goa and Macao in the 16th Century ; The Untold Story of Leonor da Fonseca, A Macanese New Christian (1593-1595) - Morais, Isabel (澳门学引论, 2010)

The Chinese Diaspora in Mozambique - Morais, Isabel (Singapore: The Chinese Heritage Centre Bulletin, 2005)

Smallpox Vaccinations and the Portuguese in Macao - Morais, Isabel (Review of Culture, 2006)

Ruy Guerra - Morais, Isabel (Dictionary of African Biography, 2012)

O Sonho e o Desejo Libertários da "Lusa Macaense" Lee Li-Lyang: O Heterónimo Feminino na poética de Virgílio De Lemos", - Morais, Isabel Maria da Costa (Entre a Desmistificação e a utopia: Indagação sobre as Lusofonias , Macau: University of Saint Joseph.69-95, 2014)
Virgílio de Lemos (1929-2013), poeta de vanguarda, é um dos precursores da modernidade e experimentalismo como criador do “barroco estético” que ele próprio designou como a linguagem poética marcante nas letras moçambicanas no das décadas de 50 e 60

nventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country [Research Report] - Morais, Isabel; Baxter, Alan (University of Saint Joseph, 2018)

Macau entre a ‘China Tropical’ e a Lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pós-colonial - Morais, Isabel (Novas perspetivas sobre o luso-tropicalismo, Portuguese Studies Review PSR, 2018)

Macau entre a “China Tropical” e a lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pós-colonial - Morais, Isabel (Portuguese Studies Review, 2018)

Macao Caught between the "Tropical China" and Oriental-style: An Approach to the Colonial and Post-colonial Contexts/Macau entre a "China Tropical" e a lusofonia a Oriente: Algumas achegas sobre os contextos colonial e pos-colonial/Macao entre la "Chine tropicale" et la lusophonie a l'orientale: contribution a l'etude des contextes colonial et post-colonial. - Morais, Isabel (Portuguese Studies Review, 2018)
Gale OneFile includes Macao Caught between the "Tropical China&q by Isabel Morais. Click to explore.

“Little Black Rose” at the 1934 Exposição Colonial Portuguesa - Morais, Isabel (Gendering the Fairs: Histories of Women and Gender at Fairs, 2010)

Law on Race and Slavery, Brazil, 1824 -1888 - Morais, Isabel (Encyclopedia of Free Blacks and People of Color in the Americas: The African-American Heritage of Freedom, 2011)
When Columbus arrived in 1492, the first free black person--a sailor--set foot in the Americas. Over the next 400 years, as slavery spread and became entrenched in the Western Hemisphere, free blacks built communities throughout North and South America, playing a critical role in every region, colony, and country. From Canada to the Caribbean to Chile, they established vital economic and social institutions, championed the cause of abolition, and formed a bridge between the worlds of free whites and enslaved blacks. They worked as artisans, farmers, ministers, merchants, shipbuilders, and reporters. Many free blacks served in the military and fought in every major war, including the American Revolution, the Haitian Revolution, and the Latin American wars for independence. Others served in government, and some--like presidents Bernardino Rivadavia of Argentina and Vicente Guerrero of Mexico--became national leaders.Free people of color in the United States and the Americas hold a unique status in global history. Never before and never since has such a group existed in large numbers anywhere in the world. Long shrouded in obscurity and overshadowed by scholarship on slavery and race, the free black community has become a growing and vibrant field of study as historians uncover vast material on this group, revealing how they lived, how they shaped society, and how they transformed the history of every nation in the hemisphere.Encyclopedia of Free Blacks and People of Color in the Americas is the first reference book to cover this crucial subject. Arranged alphabetically, this new, two-volume encyclopedia includes articles on all major events, issues, and concepts relevant to the free black community in the United States from the colonial period to the Civil War and in the rest of the Western Hemisphere from the late 1400s to the late 1800s, when emancipation became universal. Nearly 400 articles cover every country, colony, state, city, and region in the Americas with a significant presence of free blacks, and biographies, thematic articles, and entries on related subjects shed light on this fascinating topic. Featuring primary sources, illustrations, maps, tables, charts, a chronology, cross-references, suggestions for further reading, and a bibliography, this unique, original, and groundbreaking encyclopedia provides a wealth of information not available anywhere else.Entries include:-Abolitionist movement in Brazil -Zabeau Bellanton -Captain Cudjoe -Coffee cultivation -Education and literacy -Forten family -Free black artisans -French Caribbean -Gender attitudes -Guerrero (slave ship) -Haitian Revolution -La Escalera Plot -Laws of free birth -Legal discrimination on the basis of race -Living "as free" -Toussaint Louverture -Maroons -Marriage between free and slave -Midwives and traditional healers -Negro Convention Movement -Rebecca Protten -Somerset v. Stewart.

Jan Jacob Slauerhoff’s the forbidden realm: in Camoes’s footsteps from Lisbon to Macau - Morais, Isabel (The City and the Ocean: Journeys, Memory, Imagination, 2012)

Inventory of Portuguese-based Intangible and Tangible Heritage in Larantuka and Sikka (Maumere) in Flores Island (Indonesia): Legacies and Realms of Memory of Portuguese Eurasian Communities in a Muslim Country - Morais, Isabel; Baxter, Alan N. (University of Saint Joseph, 2018)
A study of Portuguese cultural vestiges assimilated into the local cultures of the island of Flores, in Eastern Indonesia, and maintained today. The vestiges include, principally, street theatre (the Bobo tradition) as well as ritual traditions inherited through the Confraternities established by Dominican missionaries in the 16th century.

Images of Law in Chinese Crime Fiction - Morais, Isabel (2014)
Crime fiction in China emerged in the 1890s in translations of Western works, and evolved from the mere imitation of Western crime fiction to becoming an autonomous literary genre. Despite fluctuations in popularity, the genre of Chinese crime fiction, the plots of which are based on true cases, has retained a reasonably constant presence on the literary scene, and has captured the popular imagination in contemporary China and, more recently, across the world. After the demise of Mao, under whose governance the genre was banned, the government of the early Deng regime began to favor so-called “legal system literature” (fazhi wenxue), and aimed to use it to propagate moral principles and maintain political control in opposition to writers who strived for independence and originality. Since the mid and late 1980s, which were considered the heyday of Chinese crime fiction, and the expansion of the legal system and legal institutions, crime fiction has served to illuminate the role of law and to display new social perceptions. To investigate these attitudes, I focus on works of contemporary Chinese crime fiction by arguing that they are expressions of a confluence of cultural exchange and new trends. Several factors may have contributed to such a change, from the impact of the cinema and television serials in China to the celebrity status of Chinese detectives, lawyers and judges both as crime solvers and writers in the Chinese mainland and amongst the Chinese writing diaspora. An important finding is that besides giving detailed descriptions of legal procedures, all of the works studied have clearly shifted away from the traditional formula of Chinese crime fiction, that is, of the quest of a hero for justice, punishment, and revenge, to focus on the process of solving crime and the rendering of justice through legal processes. It seems that crime fiction is becoming crucial in conveying a new understanding of citizen’s rights in an attempt to fit into ongoing contemporary debates on universalistic notions of justice and the competence of legal institutions to provide justice to increasingly marginalized sectors of contemporary China.

Henrietta Hall Shuck: Engendering Faith, Education, and Culture in Nineteenth-century Macao - Morais, Isabel (Americans and Macao: Trade, Smuggling, and Diplomacy on the South China Coast, 2012)
Chapter 7 Henrietta Hall Shuck Engendering Faith, Education, and Culture in Nineteenth-Century Macao Isabel Morais Introduction Henrietta Hall Shuck (1817–1844) is famous for being the first American female missionary in China. Despite her short period of residence in Macao in the early nineteenth century, her multiple experiences in the Portuguese colony are invaluable. Her pronouncements in her journal entries, correspondences and other writings make clear her perceptions of Christian interaction with the Chinese people. Her writings combine strong religious beliefs with an equally powerful commitment to promote gender equality through education . Excerpts from her journal openly address female child slavery, the mui tsai system (little girls sold as household servants and for prostitution), gender-based class hierarchies, and the exploitation of women and children. Henrietta helped establish the first Chinese girls’ school in Macao and promoted other important factors through her writing such as the “Camões’s Garden and Grotto” and her discussion of The Lusiad. Had Henrietta Hall not come to China, I might not be here today.1 The first four decades of the nineteenth century were critical years in the Pearl River Delta and Macao. Many examples show Chinese tightening political control over Macao and increased opposition to British incursions.2 In Portugal, several reforms aimed at reinforcing state control of the administrative, political, military, and economic colonial organizations were implemented and extended to Macao.3 In 1835, the governor of Macao ordered that Portuguese who were born in Macao or who had lived in Macao for a long time, be 106 Isabel Morais restricted to municipal affairs only and thereby reducing the political autonomy of the local elites.4 Meanwhile, other important legislation was also extended to Macao. A law passed in 1834 called for the dissolution of all religious orders and congregations, and the abolition of slavery in every Portuguese territory in 1836. These initiatives weakened the Catholic Church’s role in the education system since all schools for both Portuguese and Asian converts in Macao were church-affiliated under the Portuguese Padroado (Patronage) system in Asia.5 At the same time, the United States’ maritime expansion and foreign policy in Asia started to assume a more assertive role, promoting American social, political, and liberal ideas. In 1803, the governor of Macao prohibited the consul of the United States from spending the winter in Macao, forcing him to go to Canton.6 Driven by profits from trade, Americans were nonetheless encouraged to continue going to China, and despite restrictions in Macao, they used the city as a base for not only commerce but the promotion of religion as well. This was done despite the opposition of the British East India Company to missionary activity, the Chinese government’s prohibitions of publicly propagating religion and the local Catholic elite’s aversions to non-Catholics in the Portuguese colony.7 According to Reverend John Lewis Shuck, Henrietta’s husband, the Protestant missionaries in Macao were “strictly prohibited by the civil authority any public efforts for the diffusion of the gospel” being limited to personal conversations only.8 The persecution against Protestants in Portugal might have contributed to the intolerance among Roman Catholics in Macao. It is worth mentioning that between 1843 and 1846 around one thousand Jews fled from Portugal to the United States and West Indies (British island of Trinidad). In 1846 more than four hundred Jewish people fled from the Portuguese archipelago of Madeira to Jacksonville and Springfield, in the state of Illinois.9 On the other hand, the immigration of Catholics into the United States, resulted in the so-called “nativist” movement in the 1840s, and the rise of the anti-immigrant Know-Nothing Party of the 1850s.10 For many years Protestant missionaries in China were restricted to Guangzhou (Canton) and Macao. They concentrated on distributing literature among members of the foreign and Chinese merchant class, which gained a few converts. And they laid the foundations for more humanitarian efforts of advancing education in China among the lower classes and providing medical services to the needy. This situation would change after the Opium Wars led to Henrietta Hall Shuck 107 the imposition of treaties, and compelled the Chinese government to allow evangelization and freedom to convert Chinese to Christianity. In the 1830s, North American and British missionaries established bases in Macao to advance their evangelical operations. Amidst the restrictions and constraints of the diplomacy of the Canton system (ca. 1700–1842), which included a ban on foreign women entering China...

Francisca Diniz - Morais, Isabel (Feminist Writings from Ancient Times to the Modern World: A Global Sourcebook and History [2 volumes], 2011)
Collecting more than 200 sources in the global history of feminism, this anthology supplies an insightful record of the resistance to patriarchy throughout human history and around the world.From writings by Enheduana in ancient Mesopotamia (2350 BCE) to the present-day manifesto of the Association of Women for Action and Research in Singapore, Feminist Writings from Ancient Times to the Modern World: A Global Sourcebook and History excerpts more than 200 feminist primary source documents from Africa to the Americas to Australia.Serving to depict "feminism" as much broader—and older—than simply the modern struggle for political rights and equality, this two-volume work provides a more comprehensive and varied record of women's resistance cross-culturally and throughout history. The author's goal is to showcase a wide range of writers, thinkers, and organizations in order to document how resistance to patriarchy has been at the center of social, political, and intellectual history since the infancy of human civilization. This work addresses feminist ideas expressed privately through poetry, letters, and autobiographies, as well as the public and political aspects of women's rights movements.More than 200 chronologically arranged entries on feminist writers, thinkers, and organizations across 4,000 years of human historyContributions from more than 100 international scholars, including historians, sociologists, literary, cultural theorists, religious scholars, writers, and activistsBrief bibliographies of further readings, websites, and other relevant resources with each entryLists of entries arranged by region as well as by broad topic, in addition to a comprehensive index
Keywords: Social Science / Ethnic Studies / General; Social Science / Feminism & Feminist Theory

Dos Santos Albasini, João (1876–1922) - Morais, Isabel (The International Encyclopedia of Revolution and Protest, 2009)
Born in Magule, Mozambique (Portuguese East Africa), João dos Santos Albasini was a mulatto, the leading intellectual in the main center, Lourenço Marques (today, Maputo), the editor of O Africano (The African) founded 1908, and O Brado Africano (The African Voice) founded in 1918, and a champion of worker and African rights. Often characterized as a republican and a moderate, Albasini had a basic education and an appetite for ideas. He was an avid reader of republican theory, syndicalism, and anarchism – all influential in Portugal – and was familiar with a range of radical ideas circulating in the city's thriving café culture.
Keywords: 1800-1899; 1900-1999; Africa; Southern Africa; bibliography; colonialism; comparative history; imperialism; political history

Darwinism, Freemasonry and print culture: The construction of identity of the Macanese colonial elites in the late nineteenth century - Morais, Isabel (Macao - The Formation of a Global City, 2013)
In his most quoted study Imagined Communities, Benedict Anderson argues that the invention of the printing press and the rise of print media contributed to a textual representation of the concept of the nation and nationalism. He states that ‘popular’ print culture was also crucial in its contribution to a global exchange that would have reinforced the idea of an ‘imagined community’.1 Anderson further explains that before the eighteenth century, the concept of nation was extensive, as Latin was the language of a broad, vast, imagined community called ‘Christendom’, but as there were changes in the religious communities, such a concept began to be replaced by French and English as vernacular languages of administrative centralization.2 Thus, print capitalism allied to the book market supported by the improvement of communications and the emergence of new and diverse forms of national languages, originated the creation of clusters of small creole ‘imagined political communities’ that were eager to promote new forms of national and cultural consciousness, aimed at widespread literacy through liens of kinship, ethnicity, fraternity, and power loyalties.3 This chapter posits that Anderson's arguments regarding creole nationalism in the new world, fit the particular case of the emergence of the printing, publishing and book-selling culture among a Euro-creole bourgeoisie from Macao with solid kinship, ethnic, commercial and social connections in Hong Kong, Canton, Shanghai and other littoral spaces in the treaty ports in East Asia, and takes these developments as a necessary point of departure. I argue that they used the widespread nature of print media to empower themselves and other community members with the progressive eighteenth-century Enlightenment ideas on rational scientific knowledge. They embraced atheism and anti-clericalism as important elements of enlightenment, thus promoting scientific culture, constitutional monarchy or republican forms of government, social mobility for ethnic minorities, and religious and intellectual tolerance that to a certain extent challenged the Catholic Church and conservative circles.

“China Wahala”: the Tribulations of Nigerian “Bushfallers” in a Chinese Territory” - Morais, Isabel (Transtext(e)s Transcultures 跨文本跨文化. Journal of Global Cultural Studies, 2009)
Recent scholarly studies and media coverage have primarily focused on China’s increasing presence and sometimes asymmetrical engagement with Africa in tandem with the new trend of Chinese migration to that continent. Yet, the inverse flux of Africans to China and the emergence of African communities in Southern China over the last decades is influencing some areas of the Pearl River Delta Region, and changing the fabric of cities like Guangzhou, Macau and Hong Kong, in a way without precedent. There are representations or exotic descriptions from some mass circulation magazines and newspapers on the infamous Chungking Mansions in Hong Kong or the so-called “Chocolate-city,”an area centered aroundHongqiao, the village-district and Canaan market in the city of Guangzhou, with its arcades and strip malls filled with ethnic businesses and transnational migrants. In Macau, significant concentrations of African population of different origins are also seen in the “Papa pun” commercial center or in downtown areas. Despite many studies devoted to the “ethnoburbs” in other latitudes, only very recently, these entrepreneurial African communities in Mainland China are starting to become worthy of serious scholarly attention. Yet,there is total absence of studies dealing with the presence of more and more African students and the cultural manifestations of African communities well portrayed in the new African cinema, in music produced by Afro-Chinese bands or even singers.Besides a continuing inward flow of transient Africans who come to China for business on a regular basis, a significant number of settler African traders, particularly Nigerians, have already married local Chinese women, set up families, autonomously run their businesses without recourse to Chinese intermediaries, and established a web of informal and formal committees representing their home nations and states, to solve disputes while maintaining personal and business links with Africa. Besides, those emigrant ‘bushfallers’ who are coming to China solely for business purposes, a new form of “silent” migration of Nigerians comprising students from different backgrounds is enrolling in higher education institutions in the Macau Special Administrative Region of China. These students are coming to pursue their studies or to seek a job to pay their student fees at the margin of the PRC scholarship and stipendprograms for visiting African students that were popular in China in the 1960s and mid-1970s as part of CCP’s foreign policy for Third World aiming friendly relations with Africa. Today, these “transnational” Nigerian students are in their own way affirming their identity and difference, in southern China, in particularly in Macau SAR, thanks to their network of multiple interrelations across nation-states from Africa to Asia and to a combination of perseverance, zeal, and gentleness without subservience. Although they have not been targets for the hostility and even violence like the Shanghai incident of July 1979 or the Nanjing protests in December 1988 at Hehai University targeting African students, today these Nigerian students are facing more subtle forms of ethnocentrism and legal discrimination from immigration laws to daily practices, which always try to associate their citizenship to problematic or easy stereotypes of scam or colour. Yet, at the same time, everything seems to indicate that these newcomers are quick adapting and finding new forms of negotiating their social integration in the Chinese local society which in turn is offering more opportunities.This paper is part of a more ambitious project which aims to assess the new forms of migration from Africa to China and from China to Africa as well as their impact and contribution of globalization. First, this paper considers why and how Macau has evolved from a Portuguese outpost where slavery was a an institutionalized commodity to special administrative region of China where a new urban African community, mostly composed by Nigerian students, is in formation due to opportunities and rapid changes occurring in the region in the first years of the twenty-first century, by comparing the new to old African communities of students and business people/migrant workers from former Portuguese colonies (Angola, Cape Verde, São Tomé and Príncipe, Guinea-Bissau, and Mozambique).Finally, borrowing the title from a sequel movie with the same title of the promising New African cinema, the paper focus on the “China Wahala”or the troubles of these Nigerian students through their tales of their experiences of racism(s) and their negotiations and responses which radically contradicts not only the slogans of cultural diversity propagated by the official discourse and tourist channels as these Nigerians are confronted daily with often dramatic situations ranging from indifference and ostracism to exclusion.

Breve Abordagem ao Percurso Vivencial e Poético de Um ‘Autor Maldito’: Carlos Augusto Montalto de Jesus (1863-1932) na China e pelo Mundo Fora - Morais, Isabel (Mapas Esquivos” no Centenário de Sophia de Mello Breyner Andresen (1919-2019): Navegação a Oriente, 2022)

Binding Ties of Miscegenation and Identity: The Narratives of Henrique Senna Fernandes (Macao) and Rex Shelley (Singapore) - Morais, Isabel Maria Da Costa (Portuguese and Luso-Asian Legacies in Southeast Asia, 1511–2011, vol. 1: The Making of the Luso-Asian World: Intricacies of Engagement, 2011)
Vários “pequenos” portugueses fizeram sentir a sua presença na “imensa Asia”, uns quase como reis, alguns como escravos, o maior número simplesmente como portugueses capazes de amar mulheres orientais e ser por elas amados. Capazes de fecundar mulheres de cor e fazer sair dos seus ventres portugueses também de cor.(Several “small” Portuguese made felt their presence in the “enormous Asia”, some as almost kings, others as slaves, the great majority just as Portuguese [who were] able to love oriental women and be loved by them. [They were] able to inseminate women of colour and to make their wombs produce other Portuguese also of colour.)Gilberto Freyre, Aventura e RotinaDespite the dynamics of globalization and rapid economic and political development, it is still noticeable nowadays that several Portuguese creolized communities in postcolonial societies have resisted cultural homogenization, particularly those scattered throughout the detached, peripheral regions of East and Southeast Asia that were under the Estado da Índia's sovereignty and influence (Goa, Daman, Diu, Sri Lanka, Malacca, Macao and Timor) and that the Portuguese created alongside the local political authorities (Indonesia and today's Singapore).By the beginning of the seventeenth century, the official population in the colonies of several territories in Asia that proudly claimed Portuguese ancestry had reached nearly one-and-a-half million individuals, as a legacy of colonial (dis)encounters. Centuries later, the Portuguese descendants of this “shadow empire” forged through trading, matrimonial alliances and cultural networks — notwithstanding a pragmatic adaptation to times of unprecedented political, economic and cultural upheaval — persist in a quest for identity and cultural reaffirmation of “Portuguese” cultural differentiation, which continues to be faithfully perpetuated and transmitted, centuries after the earlier Portuguese contacts ceased. These communities show distinctive aspects of what could be called a certain “Luso-Eurasianness”, exhibited in oral literature, religious practices, family surnames, ceremonies, cuisine, public structures, ways of speaking and, above all, in identity-making religious and cultural reinterpretation of lived and shared commonalities.This study argues that, even if relatively scant attention has been paid to the literary production of the communities considered here, in particular in Anglophone postcolonial studies, they have influenced and continue to exercise seminal influence on most postcolonial imaginaries, either in their respective societies or in the contemporary fiction of the Luso diaspora.

African Female Nascent Entrepreneurship In The Macao S.A.R. - Morais, Isabel (Urban Anthropology and Studies of Cultural Systems and World Economic Development, 2014)
African women from different countries and social classes, from those seeking refugee status to diplomats and peasants' daughters, have been arriving in increasing numbers on Chinese shores since the 1980s. The amazing stories of some of these "invisible" but dynamic women have been ignored, yet they reveal great diversity and deserve scholarly attention, as they provide rich material for studies on the African diaspora in China. This article focuses on African migration to Macao, a former Portuguese colony and primary migration destination in the Pearl Delta River Region, which currently hosts the densest African population in China. It explores both the more recent and the relatively longer-term migration of African women and university students to Macao, and examines the intersection of these communities resulting from the overlap between the ongoing global movements of African diasporas and new African migratory trends to China. The article draws on the life stories as well as the educational and entrepreneurial experiences of African women in Macao, and investigates the relevance of ethnic networks of trust and reciprocity for their communities' survival. This article places specific emphais on the experiences of African women, recognizing their achievements in the face of multiple intersections of racism and sexism on the part of both state and society, and reveals how the women employ a resistance strategy by reinforcing ethnic migrant networks.

A symbologia Chinesa nos contos de antonio torrado: uma breve abordagem a recepcao da literatura infanto-juvenil em Macau e na China - Fong, Mei Ian (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Lusophone Studies in Linguistics and Literature (MLLS); University of Saint Joseph

A proposal for a revitalization plan for camoes area in Macao and its surrounding community through a humanistic approach - Lei, Mei Kei (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph